Vaccine distribution network opportunities on a national scale - Seprényi, Kitti; Veres, Péter; Cservenák, Ákos (Advanced Logistic Systems - Theory and Practice, 2023)
Building an effective distribution network is a significant advantage for any company. This is especially true for easily damaged or perishable items, where the length and speed of the transport, as well as the loading time, play a major role in maintaining quality. In this article, we examined the transport/distribution options for the creation of a vaccine distribution network in Hungary, which can meet strict rules. We took into account the driver’s working hours, the maximum delivery time of the vaccine, the storage options of the county seats, and as a result we got the most efficient distribution plan of Hungary. To solve the problem, we use conventional-, greedy-, and heuristic algorithms, which were compiled by Excel and its SOLVER extension.